The Influence of Customer Relationship Management and Digital Marketing on Customer Satisfaction in the E-Commerce Industry with Customer Experience as a Moderator - Kamaruddin, Muhammad Junaid (Journal of Business and Behavioural Entrepreneurship, 2025)
This study aims to prove whether there is an influence of customer relationship management and digital marketing on customer satisfaction in the e-commerce industry with customer experience as a moderator. In the context of e-commerce, customer satisfaction can maintain loyalty and increase sales. This study involved 150 respondents. The analytical method used is Structural Equation Modeling (SEM) with Smart PLS (Partial Least Square) software. The research results show that customer relationship management has a positive and significant effect on customer satisfaction in the e-commerce industry, where a good relationship between the company and customers can improve the shopping experience. Apart from that, digital marketing has also proven to be significant in customer satisfaction by utilizing digital channels to interact. Thus, customer experience as a variable does not strengthen as a moderator in the relationship between customer relationship management and digital marketing on customer satisfaction in the e-commerce industry. This shows that although customer experience is important in building positive interactions with e-commerce platforms, this factor is not strong enough to strengthen the influence of customer relationship management and digital marketing directly on customer satisfaction.